Quality-Based Differentiation Mediating Entrepreneurial Orientation and Marketing Performance - Situmorang, Tumpal Pangihutan (Graduate Program Magister Manajemen Pendidikan, 2023)
This research aims to explore the variable Quality-Based Differentiation to overcome the gap in entrepreneurial orientation in improving marketing performance rooted in the resource advantage theory of competition (RAToC). The survey method was used to collect data after inviting 264 owner-managers of small and medium enterprises (SMEs) to participate in this study. The AMOS structural equation modeling software tests our proposed hypothesis. The quantitative analysis resulted in the acceptance of the proposed hypothesis with several significant findings. The most important finding is that companies must invest in developing their resources in order to be able to produce differentiated products based on quality so that it will become a lever in improving marketing performance. A strong entrepreneurial orientation complemented by solid quality-based differentiation supports business strength in achieving a superior competitive position in the market.